A review on the preparation of anode materials and anode films for solid oxide fuel cell applications. (14th April 2021) - Hadi, Nur Hanisah; Somalu, Mahendra Rao; Samat, Abdullah Abdul; Muchtar, Andanastuti; Baharuddin, Nurul Akidah; Anwar, Mustafa
Summary: The primary components of SOFCs are the anode, cathode, and the electrolyte. Anode is critical in achieving the effective electrochemical oxidation of fuel; thus, its performance can be improved using homogenous powder synthesized through an appropriate method. Various synthesis methods, including solid‐state reaction and wet chemical methods have been used to synthesize anode materials. However, each technique has several advantages and disadvantages. Given that anode is a porous electrode, few criteria, such as high conductivity, tolerance towards carbon deposition, chemical stability, and thermal stability, must be fulfilled. Researchers also modified the existing synthesis method to improve the performance of the anode. In addition, various anode fabrication techniques including physical and colloidal deposition techniques are briefly discussed to understand their effect on the performance of the deposited layers. The aim of this review is to discuss the various anode synthesis and deposition techniques and their influence on the properties and performance of SOFCs. Abstract : Modification of synthesis method helps to improve the material properties. Solid state method is an inexpensive method to produce a large amount of powder. Sol‐gel is a low‐cost method but requires expensive starting materials. Hydrothermal is a suitable synthesis method to produce high homogeneous powders. GNP is a low‐cost method but produces ash and smog that reduces the yield. Co‐precipitation is the simplest synthesis way and consumes little starting materials. Physical fabrication is more expensive than the colloidal fabrication technique.